The Concept of gamification, metaverse & AI to develop hybrid learning systems inside education - Gamayanto, Indra; Wibowo, Sasono; S, Dewi Agustini; Prayitno, Agus (IJISTECH (International Journal of Information System and Technology), 2024)
The development of information technology has reached its peak, where AI has transformed and influenced many things, one of which is the world of education, especially universities. In this concept research, we will describe in a big picture how smart gamification, metaverse, and AI will influence and how to build this so that it can gradually change our teaching and learning patterns. Of course, this has been resolved in the book we published on Amazon. Therefore, if readers want to know and understand more deeply, they can read the book we created to apply it. The results of this concept research are formulas, frameworks, and the maturity level to be able to develop hybrid learning systems, which may be used to the way we teach, the way we give assignments, and the way we test, as well as other things related to business processes at the university. Therefore, we need to change what already exists so that it can be adapted to the situation and conditions of information technology development and the current globalization competition